UJI POTENSI ANTIFUNGI ISOLAT ACTINOMYCETES DARI KEBUN RAYA BOGOR TERHADAP PERTUMBUHAN MALASSEZIA FURFUR - Rochima Nuzul Haq (2021)
Malassezia furfur is a normal flora fungus on human skin, but it can cause Pityriasis Versicolor disease. The antifungal drugs that used to treat Pityriasis Versicolor were resistance. Actinomycetes are Gram positive bacteria which are generally saprophytic in the soil and capable of producing antifungal compounds. This study aims to determine the potential of Actinomycetes isolates from the soil of Kebun Raya Bogor as an antifungal towards M.furfur growth. Actinomycetes were grown on Strach Casein Agar (SCA). The Actinomycetes isolate will be diluted gradually into concentration groups 10^-1; 10^-2; 10^-3; 10-4; 10-5; 10-6. Testing of Actinomycetes isolates as antifungal towards M.furfur was carried out on Sabouraud Dextrose Agar (SDA) using the in vitro disc paper diffusion method. The 24 hours incubation time resulted in an inhibition zone that was larger than 48 hours. The inhibition zone was only produced by the concentration groups 10-1; 10-2; 10-3 with each an average diameter of 2.61 mm, 2.25 mm, and 2.10 mm. The Kruskall Wallis test results obtained a significance of p<0.005, where there was difference in the mean zone of inhibition between the two groups in inhibiting the growth of M.furfur. Antifungal compounds produced by Actinomycetes have several effects in inhibiting fungal growth, including inhibiting ergosterol synthesis and disrupting the permeability of fungal cell walls.